(untitled) (PANGEEA, 2025)
Along of Arieş Valley, in Apuseni Mountains. Apuseni Mountains territory has a rich and varied background of natural resources, its geographical components of the landscape with important attributes defined by the relatively high number and density of valence aesthetic, scientific, recreational and educational degree. These meanings have made the territory’s natural heritage, its original values , to represent the main elements to attract and retain tourists. This paper aims to present principales tourist attractions of Aries Valley.